Voices of the Indigenous Marginalized Community in Bina Thing’s Yambunera - Rai, Bidur (INTELLIGENCE Journal of Multidisciplinary Research, 2023)
The article studies the voices of the indigenous marginalized community in Bina Thing’s Yambunera from a Subaltern perspective. Yambunera has included thirteen stories and this article tries to explore the voice of the indigenous marginalized people and their representations only in six stories. Bina Thing attempts to bring into the mainstream literature the cultural dissimilarities prevalent in Nepali society. Characters portrayed in Yambunera are marginalized and silenced because of dominant culture, cultural dominance, poverty and illiteracy. The article intends to argue the ethnic identity issues, marginalization, discriminatory social practices and subordination to the rulers in the selected text. Thus, the study critiques the text from the critical perspectives of Gayatri Chakravorty Spivak and J. Maggio. Basically, Subaltern Studies explores the voices of the marginal groups in society and examines how the literary discourse represents these voices. Spivak argues that class consciousness is self-alienating the social groups from the others within a domain of exploitation and domination. The article tries to examine issues such as injustice, prejudice, protest, and resistance in the text and intends to shed light on the voices of the indigenous women. Yambunera focuses on the plights of the Tamangs living in Yambu who are perceived as being uncultured, savage and uneducated and, above all, they are silenced. The findings of the discussion indicate injustice, prejudice, protest and resistance in the case of the fictionalized characters in Yambunera. Furthermore, the study reflects the search for cultural identity and the marginalized people’s efforts to stand up for the voices. The present article encourages a good understanding of the marginalized voices in Nepali literature.